Aflatoxins - Occurrence, Detoxification, Determination and Health Risks 2022
DOI: 10.5772/intechopen.96893
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Indigenous Processing Methods on Aflatoxin Occurrence in Africa

Abstract: Aflatoxin is a major mycotoxin naturally produced in plants. Various postharvest treatments such as drying, storage materials and storage conditions have shown to influence the accumulation of this toxin in food crops. Beside indigenous processing methods including fermentation, roasting, and cooking have contributed to the reduction in aflatoxin expression. Although these methods are not used in exclusion, each stage has an inherent impact on the levels of aflatoxin in the final products. This chapter reviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Consequently, developing effective technologies for decontamination of wheat containing aflatoxins has gained considerable interest in scientific and economic communities. Previous works investigating the effect of fermentation on the levels of aflatoxins in fermented wheat doughs indicated that this process could reduce levels of aflatoxin in final products (Noroozi et al, 2020(Noroozi et al, , 2022Rashid Hudu et al, 2022).…”
Section: Preparation Of Wheat Doughmentioning
confidence: 99%
“…Consequently, developing effective technologies for decontamination of wheat containing aflatoxins has gained considerable interest in scientific and economic communities. Previous works investigating the effect of fermentation on the levels of aflatoxins in fermented wheat doughs indicated that this process could reduce levels of aflatoxin in final products (Noroozi et al, 2020(Noroozi et al, , 2022Rashid Hudu et al, 2022).…”
Section: Preparation Of Wheat Doughmentioning
confidence: 99%
“…More than 300 types of toxic fungal metabolites have been identified, although the most relevant and known mycotoxins include the aflatoxins (AFs) (AFB 1 , AFB 2 , AFG 1 , AFG 2 ), deoxynivalenol (DON), zearalenone (ZEN), ochratoxin (OTA), and fumonisins (FBs) (FB 1 , FB 2 , FB 3 , among others), which are highly stable metabolites that can resist food processing [2] and therefore remain in the final products. Consequently, various strategic pre-processing methods are adopted to reduce mycotoxins in the food chain [3]. Due to their remarkable toxicity and associated health risks, the threshold levels for mycotoxins have been regulated worldwide [2,4,5].…”
Section: Introductionmentioning
confidence: 99%